2015
DOI: 10.5941/myco.2015.43.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Cladosporiumcladosporioides andC. tenuissimumCause Blossom Blight in Strawberry in Korea

Abstract: Blossom blight in strawberry was first observed in a green house in Nonsan, Damyang, and Geochang areas of Korea, between early January to April of 2012. Disease symptoms started as a grey fungus formed on the stigma, which led to the blossom blight and eventually to black rot and necrosis of the entire flower. We isolated the fungi purely from the infected pistils and maintained them on potato dextrose agar (PDA) slants. To test Koch's postulates, we inoculated the fungi and found that all of the isolates cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 25 publications
1
27
0
3
Order By: Relevance
“…Las características corresponden con las reportadas para esta especie por Mapook et al (2020). 3) En Didymella glomerata, las colonias inicialmente fueron de color blanco, posteriormente se tornaron de color disarticulate easily, mostly unseptated, elliptical to lemon-shaped, pale to maroon-olive green and smooth, sized 3.0-5.5 × 2.5-3.0 µm, these characteristics were consistent with reports by Bensch et al (2010), Bensch et al (2012 and Nam et al (2015). 2) Aplosporella hesperidica showed culture with slightly elevated mycelia, with white aerial hyphae on the surface, extending from the center, obverse of the white culture.…”
Section: Fully Bilingualsupporting
confidence: 89%
See 2 more Smart Citations
“…Las características corresponden con las reportadas para esta especie por Mapook et al (2020). 3) En Didymella glomerata, las colonias inicialmente fueron de color blanco, posteriormente se tornaron de color disarticulate easily, mostly unseptated, elliptical to lemon-shaped, pale to maroon-olive green and smooth, sized 3.0-5.5 × 2.5-3.0 µm, these characteristics were consistent with reports by Bensch et al (2010), Bensch et al (2012 and Nam et al (2015). 2) Aplosporella hesperidica showed culture with slightly elevated mycelia, with white aerial hyphae on the surface, extending from the center, obverse of the white culture.…”
Section: Fully Bilingualsupporting
confidence: 89%
“…La identificación y descripción morfológica de los aislamientos se realizó con preparaciones temporales y permanentes que se observaron bajo microscopio compuesto (Virtue-N), la morfología y tamaño de 100 esporas de cada uno de los aislamientos a una magnificación de 40X. Para la determinación de la especie se siguieron claves taxonómicas y comparación con reportes existentes en la literatura científica (Boerema, 1993;Bensch et al, 2010;Bensch et al, 2012;Chen et al, 2015;Nam et al, 2015;Pan et al, 2018;Mapook et al, 2020).…”
Section: Fully Bilingualunclassified
See 1 more Smart Citation
“…Therefore, Bacillus , especially B. aryabhattai , may exert beneficial roles via the secretion of effector molecules such as anti-parasitic antibodies [ 15 50 51 52 ]. However, the commonly distributed fungal Cladosporium species found in this study have been reported to have potential for plant pathogenicity [ 38 53 ]. Therefore, these fungal species could be critical in controlling pathogenic outbreaks, and thus further pathogenicity studies (i.e., disease-causing assays) in Cladosporium are required.…”
Section: Resultsmentioning
confidence: 99%
“…Early symptoms of gray mold included brown spots on ower petals and were followed by gray conidia covering owers and fruits [61]. Blossom blight appeared as gray fungal growth on ower pistils and stamens and as infected, malformed or misshapen fruits [62]. Differences in disease incidence among an untreated control and treatments with 2% glutamic acid or L-asparagine were analyzed by followed by the paired ANOVA and compared for mean separation with the untreated plots with Tukey's HSD (P = 0.05).…”
Section: Disease Incidence Of Gray Mold and Blossom Blight And Qpcr Omentioning
confidence: 99%